Development and implementation of venous thromboembolism stewardship across a hospital network. (November 2021) - Chong, Julianne; Curtain, Colin; Gad, Fady; Passam, Freda; Soo, Garry; Levy, Russell; Dunkley, Scott; Wong Doo, Nicole; Cunich, Michelle; Burke, Rosemary; Chen, Vivien
Highlights: Venous thromboembolism (VTE) stewardship in hospital is valuable. Improvements in VTE risk assessment and prescribing achieved. Use of electronic clinical decision support associated with improved prescribing. Abstract: Background: Venous thromboembolism (VTE) is a leading cause of preventable death in hospital. Ensuring all hospitalized patients are assessed for VTE risk and given appropriate prophylaxis can reduce the burden of VTE on patients and the healthcare system. This is the first study to explore the effectiveness of a VTE stewardship program using electronic clinical decision support (eCDS) to provide oversight of hospital initiatives to prevent VTE. Aim: To determine if a VTE stewardship program can increase risk-appropriate VTE prophylaxis, VTE risk assessment using eCDS, any documented risk assessment and risk assessment within 24 h of admission, plus reduce the incidence of hospital acquired VTE (HA-VTE). Methods: Education, daily medication chart auditing, weekly clinician performance feedback, health promotion and gamification were deployed over 6 months by two multidisciplinary VTE stewardship teams across four hospitals. Service impact was assessed through cross-sectional audits of electronic medical records every 3 months and review of HA-VTE events pre- and post-intervention. Implementation costs were calculated. Results: A total of 1622 patients were audited in separate cohorts at baseline, 3, 6 and 9 months. There was significant improvement in the prescription of appropriate prophylaxis (78%, 83%, 84%, and 88%, p = 0.004), VTE risk assessment using the eCDS tool (20%, 50%, 81% and 87%, p < 0.001), any documented risk assessment (71%, 82%, 95% and 93%, p < 0.001) and any documented risk assessment within 24 h of admission (54%, 56%, 65% and 63%, p = 0.001). Use of eCDS was associated with prescription of risk-appropriate VTE prophylaxis (p < 0.001). Annual incidence of HA-VTE decreased from 7.88 to 6.99 events per 10, 000 discharges pre- to post-intervention (Odds Ratio (OR) 0.89, 95 %CI 0.66–1.18, p = 0.43). The cost of implementing the program across 133, 078 episodes of care during the study period was AUD$108, 167 (mean cost of $0.82 per patient).